Pengembangan Materi Pembelajaran Bahasa Inggris di Sekolah Menengah - M. Zaim (Fakultas Bahasa dan Seni UNP, 2001)
Abstract: This article aims at describing the possibility of developing teaching materials for Junior and Senior High Schools based on the curriculum. Some considerations in developing teaching materials are analyzed and related to tirorirs of languog, learning. It v)as proposed that some learning sources can be activated in developing teaching materials needed.Key words: teaching materiqls, learning sources, curriculum